Scientific post hoc and in situ visualisation of high-order polynomial solutions from massively parallel simulations. Issue 4 (21st April 2019) - Rasquin, M.; Bauer, A.; Hillewaert, K.
ABSTRACT: This paper presents two recent numerical tools developed respectively to perform traditional post-processing and more advanced in situ processing of high-order polynomial data generated by massively parallel finite element codes. For post-processing and visualisation of high-order solutions, we present a new ParaView plugin that integrates Gmsh used as an external library. This plugin therefore combines respectively ParaView's scalability in parallel and Gmsh's ability to apply h-refinement of the initial mesh followed by solution interpolation on the resulting visualisation grid, thus enabling parallel visualisation of any arbitrary high-order polynomial solutions in client–server mode. In a second stage, this capacity has been extended to an in situ interface based on the Catalyst library which enables in situ analysis and visualisation of high-order solutions. These new capacities are demonstrated with the visualisation of high-order solution of the unsteady flow generated by a discontinuous Galerkin method for an unsteady turbomachinery application.